Dynamics of Vascular Stiffness and Endothelial Function in Combination Therapy of Heart Failure with Preserved Ejection Fraction - Z. M. Akhilgova; I. I. Almazova; N. K. Gabitova; E. A. Kotaeva; A. G. Avtandilov (Столичная издательская компания, 2020)
Aim. To assess the effect of combination therapy (perindopril, indapamide, amlodipine) on vascular stiffness and endothelial function in patients with heart failure with preserved ejection fraction (HFpEF).Material and methods. Patients with HFpEF (n=30) were included in a nonrandomized, uncontrolled trial. All patients had a comprehensive examination: a six-minute walk test to determine exercise tolerance, echocardiography, determination of the diameter of the brachial artery with an assessment of its endothelium-dependent vasodilation (EDVD). Photoplethysmography and compression oscillometry were also carried out to assess the stiffness characteristics of vessels of various calibers and the determination of the cardio-ankle vascular index. Patients were examined initially and 16 weeks after the combination therapy order (perindopril 10 mg/day, indapamide 2.5 mg/day, amlodipine 5 mg/day).Results. The data obtained during therapy shows improvement of the endothelial function for all patients: the initial EDVD was 8.5%, by the end of the observation period it increased to 11.4% (p=0.007). A significant decrease in the systemic vascular resistance from 2591 dyn*cm-5 to 2380 dyn*cm-5 (p=0.03) and in the level of specific peripheral resistance from 32.9 dyn/sec/cm-5 to 28.5 dyn/sec/cm-5 (p=0.0051). The stiffness indices of small resistive vessels also decreased: vascular stiffness index from 10.2±2.2 m/sec to 8.4±2.5 m/sec (p<0.0001) and pulse wave reflection index from 70.2±13.5% to 61.9±14.7% (p=0.0011). Cardio-ankle vascular index (CAVI) initially amounted to 9.2±1.3 and decreased by the end of the observation period during treatment to 8.3±1.1 (p=0.0003). The pulse blood pressure was significantly decrease from 71.31±15.5 mm Hg to 64.5±12.9 mm Hg (p=0.0048) and there was a tendency to decrease in pulse wave velocity from 808 cm/sec to 730 cm/sec.Conclusion. The results of the study showed a statistically significant improvement in the elastic component of small resistive and major vessels, the endothelial function. The obtained results prove a decrease in the stiffness characteristics of blood vessels during the combination therapy.This suggests that the combination of drugs with a different mechanism of action improves not only the state of the endothelium and its function, but also significantly reduces the stiffness of the great vessels, restores the microcirculatory support of the interstitium of the myocardium and vascular wall in patients with HFpEF and leads to an improvement in the clinical status of patients with this syndrome.